Pengelolaan Bronkopneumonia Anak dengan Menggunakan Family Folder - Syahrizal, Syahrizal; Azzahra Humaira Fatin; Rosmanida Keumala Putri (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2024)
One of the developmental efforts in the health sector is improving the availability of quality health services. Health itself is a fundamental human right and a key element of prosperity that must be realized within a country. Therefore, to support comprehensive health development, the health sector provides various services, one of which is home visit. Home visits are comprehensive health services designed to promote patient and family independence, providing health care directly at the patient's residence and integrating patients and their families into planned health service activities. A home visit service activity was conducted for a patient with bronchopneumonia within the Jeulingke Health Center's operational area in Syiah Kuala District, Banda Aceh City. Supervised by supervisors from the Family Medicine Section/Department of the Faculty of Medicine, Syiah Kuala University, Banda Aceh. Home visits were performed twice per family. The objective was to evaluate treatment effectiveness and gather additional information about the patient's health status, as well as to assess the living conditions of the patient and their family. Home visit activities are complemented by the completion of the Family Folder, which includes a genogram, family life cycle, family map, family APGAR, family SCREEM, and family life line instruments.